2020
DOI: 10.1002/jhet.4132
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of glycolurils and hydantoins by reaction of urea and 1, 2‐dicarbonyl compounds using etidronic acid as a “green catalyst”

Abstract: Most of the known methods for the synthesis of heterocyclic compounds have disadvantages, such as a long reaction time and aggressive conditions. We have developed a new, rather simple and efficient method for the synthesis of a number of glycoluryls and hydantoins in water using a etidronic acid (HEDP) as "Green catalyst." So, for the first time, the condensation reaction of ureas with 1, 2-dicarbonyl compounds was carried out in the presence of HEDP. Also based on NMR studies, a chemism of these reactions, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…One of the advantages of the HEDP catalyst is that it is able to enhance the solubility of glycoluryl 1a [12], selectively destroying the crystal packing and thereby making substrate 1a readily available for reaction at the nitrogen atoms. However, the excess of HEDP leads to the formation of by-product hydantoin 3 (Scheme 3) [10][11][12], and this explains why we use as little as 2 equiv of HEDP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the advantages of the HEDP catalyst is that it is able to enhance the solubility of glycoluryl 1a [12], selectively destroying the crystal packing and thereby making substrate 1a readily available for reaction at the nitrogen atoms. However, the excess of HEDP leads to the formation of by-product hydantoin 3 (Scheme 3) [10][11][12], and this explains why we use as little as 2 equiv of HEDP.…”
Section: Resultsmentioning
confidence: 99%
“…The NMR analysis of the reaction fi ltrate (Scheme 1) (see Supplementary Information) showed that the reaction mixture contained, along with HEDP, hydantoin 3 [10][11][12] and N-nitrosohydantoin 4 (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum reported yield till date is 62 %. [46] 1 H NMR (500 MHz, DMSO-d 6 ) δ 5.05, 2.82. 13 5) was prepared by dissolving urea and benzil in ethanol and stirring the mixture for 10 minutes.…”
Section: Derivative Studymentioning
confidence: 99%